The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1371/journal.pntd.0008635
|View full text |Cite
|
Sign up to set email alerts
|

Liver damage in schistosomiasis is reduced by adipose tissue-derived stem cell therapy after praziquantel treatment

Abstract: Background In view of the potential immunosuppressive and regenerative properties of mesenchymal stem cells (MSC), we investigated whether transplantation of adipose tissue-derived stem cells (ASC) could be used to control the granulomatous reaction in the liver of mice infected with Schistosoma mansoni after Praziquantel (PZQ) treatment. Methodology/Prinicpal findings C57BL/6 mice infected with S. mansoni were treated with PZQ and transplanted intravenously with ASC from uninfected mice. Liver morpho-physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The most serious, intractable and sometimes fatal complication is granulomatosis and fibrosis of the liver caused by the embolized eggs as they are ectopically matured to embryonation [2][3][4]. Although the current control measures based on mass drug (praziquantel) administration are effective in killing adult schistosome worms [17,18], the sustained pathology due to mature eggs that have already been laid cannot be overlooked [19,20]. Hence, there is an urgent need to develop any egg-targeting strategies against pathology induced by schistosome infection.…”
Section: Discussionmentioning
confidence: 99%
“…The most serious, intractable and sometimes fatal complication is granulomatosis and fibrosis of the liver caused by the embolized eggs as they are ectopically matured to embryonation [2][3][4]. Although the current control measures based on mass drug (praziquantel) administration are effective in killing adult schistosome worms [17,18], the sustained pathology due to mature eggs that have already been laid cannot be overlooked [19,20]. Hence, there is an urgent need to develop any egg-targeting strategies against pathology induced by schistosome infection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally the MSCs were used, in combination with praziquantel, to treat S. japonicum infection in a mouse model and the treatment resulted in smaller hepatic granulomas with little tissue damage [19] . Later, Miranda et al [20] confirmed that also S. mansoni infected-mice treated with combined praziquantel and ASC had smaller granulomas and less tissue damage [20] .…”
Section: Schistosomiasismentioning
confidence: 97%
“…However, there are limited therapeutic methods in parasitic infections, and drug resistance is a challenging issue in long-term drug administration ( Ouellette, 2001 ; Montazeri et al, 2018 ; Ertabaklar et al, 2020 ). Previous studies indicated that stem cells played an important role in the treatment or control of schistosomiasis ( Miranda et al, 2020 ), malaria ( Souza et al, 2015 ), Chagas disease ( Silva et al, 2014 ), and hydatid cyst ( Abo-Aziza et al, 2019 ). Recently, Miranda et al (2020) reported that AD-MSCs could decrease liver damage in schistosomiasis through controlling the granulomatous reaction.…”
Section: The Application Of Stem Cells Therapy In Microbial Diseasesmentioning
confidence: 99%
“…Previous studies indicated that stem cells played an important role in the treatment or control of schistosomiasis ( Miranda et al, 2020 ), malaria ( Souza et al, 2015 ), Chagas disease ( Silva et al, 2014 ), and hydatid cyst ( Abo-Aziza et al, 2019 ). Recently, Miranda et al (2020) reported that AD-MSCs could decrease liver damage in schistosomiasis through controlling the granulomatous reaction. On the other hand, stem cells have been introduced as a new therapeutic option for malaria ( Wang et al, 2015a ).…”
Section: The Application Of Stem Cells Therapy In Microbial Diseasesmentioning
confidence: 99%